THE EFFECT OF YOUTUBE VIDEO ADS’ ADVERTISING CONTENT VALUE TOWARD AUDIENCE’S BEHAVIOURAL RESPONSE: CASE STUDY ON MARKETPLACE - Regine Audrea; Ferry Jaolis (Jurnal Strategi Pemasaran, 2021)
In this era of Marketing 5.0, which is full of Volatility, Uncertainty, Complexity, and Ambiguity, companies must adapt with digital in order to survive and grow. One of the most extensively used tools for communicating with the target market is social media advertising. Despite its many advantages, there are also disadvantages of advertising on social media, especially in this study, YouTube. Video advertisements on social media can be considered disturbing and lead to negative attitudes which in turn lead to unfavorable behavioral responses. For that reason, this study aims to analyze the advertising content value on YouTube video ads in terms of 4 dimension: Congruity, Credibility, Entertainment, & Informativeness in affecting audience’s attitude, which in turn influence their behavioral responses. Data were collected through online questionnaires to a total of 168 respondents from generations Y and Z, live in Surabaya and had seen at least 1 of 3 marketplace video ads on YouTube. The research data is processed using a structural model equation approach with PLS. The study's findings revealed that advertising content value in marketplace video ads influences the audience's attitude toward the ads and the marketplace brand, audience’s attitude also influences their behavioral response in a favorable and substantial way.